2019
DOI: 10.1093/ibd/izz188
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-analysis: Short-Chain Fatty Acid Characterization in Patients With Inflammatory Bowel Disease

Abstract: Background Alterations in gut microbiota and short-chain fatty acids (SCFAs) have been reported in inflammatory bowel disease (IBD), but the results are conflicting. The aim of this study was to perform a meta-analysis to explore the characterization of SCFAs in IBD patients and their potential role in the occurrence and development of IBD. Methods Case–control studies investigating SCFAs in IBD patients were identified from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(60 citation statements)
references
References 55 publications
4
45
2
Order By: Relevance
“…In patients with IBD gut SCFAs are reduced, although the results of the relevant studies could be characterized as conflicting. In a recently published systematic review and metaanalysis, Zhuang et al found significant alterations of SCFAs in IBD patients; e.g., in patients with active and inactive ulcerative colitis inverse SCFA alterations [98]. The significance of these fatty acids in the pathogenesis of IBD is further supported by the fact according to which bacteria in mucosa and feces of patients with IBD producing SCFAs are reduced.…”
Section: Short Chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…In patients with IBD gut SCFAs are reduced, although the results of the relevant studies could be characterized as conflicting. In a recently published systematic review and metaanalysis, Zhuang et al found significant alterations of SCFAs in IBD patients; e.g., in patients with active and inactive ulcerative colitis inverse SCFA alterations [98]. The significance of these fatty acids in the pathogenesis of IBD is further supported by the fact according to which bacteria in mucosa and feces of patients with IBD producing SCFAs are reduced.…”
Section: Short Chain Fatty Acids (Scfas)mentioning
confidence: 99%
“…So far, VOC analysis of faeces has shown: (i) the increase in esters of short chain fatty acids, cyclohexanecarboxylic acid and its ester derivatives associated with inflammatory bowel syndrome (diarrhoea type) [9]; (ii) the loss of short chain fatty acid in active inflammatory bowel disease [10,11] and, finally, (iii) an increase in propan-2-ol and the ratio of propan-2-ol to 3-methylbutanoic acid in colorectal cancer [12]. Urinary VOCs have unsurprisingly been proposed to be useful to detect metabolic changes in conditions involved in urological systems, for example, urinary tract infection [13], minimal change type nephrotic syndrome [14], and urological cancer detection (kidney, renal cell carcinoma, and bladder) [1,[15][16][17].…”
Section: Metabolomics and Volatile Organic Compoundsmentioning
confidence: 99%
“…In patients with ulcerative colitis, the numbers of beneficial bacteria in the intestines reduced, while the numbers of pathogenic bacteria and harmful bacteria increased (Nagao-Kitamoto and Kamada, 2017). Furthermore, studies found that the expression of short-chain fatty acids (SCFAs) in the intestinal flora of UC patients was significantly lower than that of normal people (Pohjonen et al, 2019;Zhuang et al, 2019;Danilova et al, 2019).…”
Section: Introductionmentioning
confidence: 99%